Application a case method as method of interactive training on chair of molecular biology and genetics of KAZNMU (Experimental biology, 2015)
In article questions of innovative technologies of the training, succeeded raditional methods of training are considered. Innovative activity (technology) covers all parties of didactic process: organization forms, contents and technology of training, educational cognitive activity. The method a case-stadi as the interactive method of training applied on chair of molecular biology and genetics of KAZNMU is considered in detail; in particular on the system subject “Congenital Developmental Anomalies of the Cardiovascular” at the first year.
Keywords: innovative technologies; interactive methods of training; case method; congenital defects warmly – vascular system